PENGARUH PENDIDIKAN KESEHATAN PENANGANAN DISMENORE MELALUI MEDIA VIDEO INSTAGRAM TERHADAP SKALA NYERI DISMENORE PADA SISWI SMP - Khofifah Dinta Laksana; Noor Fitriyani (Journal of Nursing Care and Biomolecular, 2023)
Introduction: Adolescent women with sexual development both physically and sexually. One of the sexual developments in adolescent women is menstruation. Dysmenorrhea is one of the menstruation symptoms. Education on the implementation of dysmenorrhea could be performed through Instagram social media.   The   study   aimed   to   determine   the   effect   of   health   education   on dysmenorrhea pain management through Instagram video media in junior high school students. The research adopted quantitative with a Quasi-Experiment design with Pre- and Post-test Without a Control Group design. The research sample was 66 respondents. The research instrument used a sheet of Observation Numeric Range Scale (NRS) Dysmenorrhea.  The Kolmogorov-Smirnov test indicated abnormally distributed with p-value (Sig) pre-test 0.000 and post-test 0.000. The Wilcoxon test obtained p-value = 0.000 (p-value <0.05). It inferred that the Health Education on Dysmenorrhea Pain Management Through Instagram Video Media affect the Dysmenorrhea Pain Scale in Students of SMP N 6 Purwodadi.   Keywords: Dysmenorrhea, Pain, Instagram Video.